(3eYLe TjhN CHj GdaVd GdHNGQis - (3eQJVj GdRHjOj , eMeO Hf eMeO Hf eMeO Hf YHO GdQRGb GdMSjfj, CHh GdajV,J (B1205 (3g` s ((3GdbOS s)
(3ChdgG (B:s
(3GdMeO ddg ceG jLH dCaVGdg s
(3BNQgG (B:s
(3aQZ ef JNQjLg SfI (B1190 (3g` s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B282 s
Keywords: (3GdJGQjNs